Quality of Freight Transport Services and Customer Satisfaction and Its Influence on Customer Loyalty - Pratiwi, Nining Diah; Suwandi, Joko (Universitas Muhammadiyah Surakarta, 2023)
The implementation of the Merdeka curriculum is one of the efforts This study aims to determine how the influence of service quality on customer loyalty freight services PT Karya Bersama Blora, how the influence of customer satisfaction on the loyalty of freight services PT Karya Bersama Blora, and how the influence of service quality and customer satisfaction simultaneously on customer loyalty freight services PT Karya Bersama Blora. The sample used was 50. The research method used in this study is a quantitative approach and explanatory research methods. The results showed that there is a significant effect of service quality variables on customer loyalty by obtaining a calculated t value of 3.227 > 2.011 (t table) or significance value of 0.002 < 0.05 and there is a significant effect of customer satisfaction variables on customer loyalty by obtaining a calculated t value of 3.782 > 2.011 (t table) or significance value of 0.000 < 0.05. From the F test can be seen that the variable quality of Service and customer satisfaction has a value of F count 41.393 > 3.19 (F table), the significance value of 0.000 > 0.05 can be interpreted that the quality of Service and customer satisfaction simultaneously affect customer loyalty.